2019
DOI: 10.21608/adjc.2019.14576.1023
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of gingival crevicular fluid levels of Chemerin and Fibroblast growth factor 21 as biomarkers of periodontal disease in diabetic and non-diabetic patients. A diagnostic accuracy study

Abstract: Background:The relation between diabetes mellitus and periodontitis has been discussed for years. Many adipokines were reported to play a major role in periodontal inflammation. Chemerin is one of these adipokines which is blamed to be involved in inflammatory conditions such as diabetes. Fibroblast growth factor 21 (FGF21) is another adipokine which is believed to induce regulation of glucose. The current study aimed to spot the light on the potential role of gingival crevicular fluid (GCF) level of FGF21 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…In addition to metabolic parameters, the main outcome of the current study demonstrated a higher level of serum FGF21 in generalized periodontitis group, when compared to group with localized periodontitis. It was in concordance with the previous report conducted in Cairo [ 18 ]. The findings suggested that the elevation of FGF21 in GCF might act as a protective mechanism to oppose periodontal inflammation in diabetic patients with periodontitis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition to metabolic parameters, the main outcome of the current study demonstrated a higher level of serum FGF21 in generalized periodontitis group, when compared to group with localized periodontitis. It was in concordance with the previous report conducted in Cairo [ 18 ]. The findings suggested that the elevation of FGF21 in GCF might act as a protective mechanism to oppose periodontal inflammation in diabetic patients with periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, there have been few attempts determining the level of FGF21 in periodontitis patients. One study showed the higher level of FGF21 in gingiva crevicular fluid (GCF) was collected from diabetic patients combined with periodontitis than those without periodontitis [ 18 ]. Moreover, after receiving periodontal treatment, the level of FGF21 in GCF was decreased, suggestive the anti-inflammation effect of FGF21 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This persistent inflammatory response is the main cause of A two-way relationship exists between PD and DM. 2 Adipose tissue is a metabolically active and complicated endocrine organ that secretes bioactive chemicals known as adipokines. As with periodontitis and diabetes, the interaction of pro-inflammatory and anti-inflammatory adipokines can result in a low-grade inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Failure of the immune system to remove the cause of inflammation results in a persistent inflammatory response and overexpression of pro-inflammatory cytokines. This chronic inflammatory response is the crucial cause of periodontitis and DM coexistence (6) .…”
Section: Introductionmentioning
confidence: 99%